EUROPEAN EEL IN KOLSKII ZALIV (Evropeiskii Ugor v Kolskom Zalive) - Konstantinov,K. G.; Sorokin,V. P. (1968)
A female of the eel Anguilla anguilla of about 1m was caught in the Kol'skiy zaliv (Kola Bay) in August 1957. Its external characteristics and the state of ovaries showed that spawning migration has begun. It is likely that the individual described penetrated into the Kila Bay from the Baltic Sea having overcome the watershed between the basins of the Kemi-Yoka and Tuloma rivers. (Author) Trans. of Zoologicheskii Zhurnal (USSR) v39 n4 p621-622 1960, by M. Slessers.